Christopher Middleton (ca. 1690-1770) - Barr, William (ARCTIC, 1983)
. He appears to have gone to sea at quite an early age, his service aboard Hudson's Bay Company ships beginning around 1719, possibly even earlier. Early in his career Middleton established his reputation as a meticulous and innovative navigator: in the spring of 1726 he published a paper in the Royal Society's Philosophical Transactions on the variation of the magnetic needle in Hudson Bay. The following year he was elected a Fellow of the Royal Society, a great honour for a ship's captain of only two years' standing. Shortly afterwards, Middleton's path crossed that of Arthur Dobbs, an influential Anglo-Irish landowner and a hard-line free trader who bitterly resented the Hudson's Bay Company's monopoly. Furthermore, Dobbs was convinced that a practicable Northwest Passage could be found via Hudson Bay and he decided to pursue its discovery, incidentally hoping to break the Company's monopoly in the process. Using his considerable influence in London, Dobbs persuaded the Admiralty to mount an expedition to search for the Northwest Passage via Hudson Bay. Further, by arranging a commission for Middleton in the Navy, Dobbs induced him to leave the company and to command this enterprise. . Leaving Churchill on 30 June 1742, Middleton's ships headed north. They discovered and entered Wager Bay but were then locked in the bay for several weeks by drifting ice. By means of boat journeys, however, Middleton established to his own satisfaction that the Northwest Passage did not lie through Wager Bay. Emerging again into Roes Welcome Sound pushed north once more, only to have his hopes dashed on reaching the cul-de-sac of Repulse Bay. Frozen Strait was still ice-covered; hence, there was no chance of pursuing the search into Foxe Basin. Having called at Marble Island for water, Middleton sailed for home, satisfied in his own mind that there was no route to the Pacific through Hudson Bay. . To Middleton we owe the exploration and mapping of Wager Bay, the northern part of Roes Welcome Sound, and Repulse Bay. Such a ...